Adiabatic plasma lenses of Morozov type with profiled magnetic field that increases its efficiency - Butenko, V.I.; Ivanov, B.I. (Вопросы атомной науки и техники, 2000)
In this work some variants of the long plasmaoptic focusing devices of Morozov type are studied.